A fault-tolerant load-balancing protocol for distributed multiserver queuing systems - Kostin, A; Oz, G (IEEE Computer Soc, 2003)
A simple and efficient scheme to achieve a fault tolerance in a new load-balancing protocol for a distributed multiserver queuing system is proposed It is assumed that the distributed queuing system consists of a job producer and a number of independent servers, or workers, who compete for produced jobs. All communications between the job producer and workers in the underlying network are based on reliable multicast. The proposed scheme is empirically investigated in a LAN of Ethernet type on a cluster of computers.
8th IEEE International Symposium on Computers and Communication (ISCC 2003) -- JUN 30-JUL 03, 2003 -- ANTALYA, TURKEY
Keywords: Communication; Recovery